2022
DOI: 10.32890/ijms2022.29.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Ostracism and Banking Employees’ Counterproductive Work Behavior in the Malaysian Banking Sector

Abstract: According to Maslow’s Hierarchy of Needs Theory, individuals should be able to satisfy their needs for belongingness in their personal and work life. Individuals recognize the value of interpersonal connection as a form of social presence. As a result, it is critical to look at negative attitude and behavior that may occur when employees are disregarded, ignored, or dismissed by the group around them. Hence, this study seeks to examine the impact of workplace ostracism on the counterproductive work behavior of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…The results indicated that the civil status of employees in Company X was not a significant factor in workplace ostracism. This contradicted previous research that has suggested that civil status could contribute to ostracism in the workplace, such as studies of Uslu (2021), Ong (2022), and Mete (2019) who found that single employees were more likely to be ostracized at work than married employees. Workplace ostracism varies, and unmarried respondents appeared to encounter more ostracism at work.…”
Section: Problem Number 3 What Is the Work Productivity Level Among E...contrasting
confidence: 87%
“…The results indicated that the civil status of employees in Company X was not a significant factor in workplace ostracism. This contradicted previous research that has suggested that civil status could contribute to ostracism in the workplace, such as studies of Uslu (2021), Ong (2022), and Mete (2019) who found that single employees were more likely to be ostracized at work than married employees. Workplace ostracism varies, and unmarried respondents appeared to encounter more ostracism at work.…”
Section: Problem Number 3 What Is the Work Productivity Level Among E...contrasting
confidence: 87%
“…They were then given the demographic sheet, the Workplace Ostracism Questionnaire, and the Emotional Exhaustion Scale to complete. Assistance was provided individually to ensure accurate and independent responses (9,11,21,22,25). Data collection involved administering the questionnaires to the participants, who were instructed to complete them independently.…”
Section: Methodsmentioning
confidence: 99%
“…CWB refers to a variety of different terms that can be seen in Table 1. All these terms have a few similar characteristics: first, the behaviour goes against the organization's usual norms or principles; second, the behaviour is harmful and poses a threat to employees and the organization; and third, the behaviour harms the organization and its stakeholders, including its employees (Ong, 2022). Also, Spector et al (2006) suggested that there are five aspects of CWB which are (1) abuse: which involves actions taken against coworkers with the intent of hurting them physically or mentally through threats, (2) production deviance: a failure to accomplish work and follow the path that is expected of them, (3) sabotage: it is taking property belonging to the company without consent, (4) theft: it involves behaviours such as arriving late to work, having a high absence rate, quitting work early, and taking extended breaks and (5) withdrawal: it is behaviour that limits the amount of time spent working to less than what the organization requires.…”
Section: Counterproductive Work Behaviourmentioning
confidence: 99%
“…When ostracism occurs in the workplace, it can cause undesirable organizational outcomes. This is because ostracism behaviour can contribute to employees behaving counter to social norms, resulting in negative behaviours (Ong, 2022). Research has shown that those who are ostracised are more likely to act aggressively and engage in deviant behaviour (Qi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%